2011
DOI: 10.1590/s1678-77572011000100010
|View full text |Cite
|
Sign up to set email alerts
|

Validation of an experimental polyurethane model for biomechanical studies on implant-supported prosthesis: compression tests

Abstract: ObjectivesThe complexity and heterogeneity of human bone, as well as ethical issues, most always hinder the performance of clinical trials. Thus, in vitro studies become an important source of information for the understanding of biomechanical events on implantsupported prostheses, although study results cannot be considered reliable unless validation studies are conducted. The purpose of this work was to validate an artificial experimental model based on its modulus of elasticity, to simulate the performance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 9 publications
(14 reference statements)
0
9
0
1
Order By: Relevance
“…Moreover, fresh mandibular specimens have a natural viscosity that hinders the attachment of strain gauges. Because of these characteristics, the application of artificial test materials for in vitro biomechanical research has been reported in the literature 3 , 5 , 9 , 10 , 12 , 16 , 24 , 28 and mathematical models have been developed to simulate the bone remodeling process under mechanical stimulus in implant supported prosthesis 13 .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, fresh mandibular specimens have a natural viscosity that hinders the attachment of strain gauges. Because of these characteristics, the application of artificial test materials for in vitro biomechanical research has been reported in the literature 3 , 5 , 9 , 10 , 12 , 16 , 24 , 28 and mathematical models have been developed to simulate the bone remodeling process under mechanical stimulus in implant supported prosthesis 13 .…”
Section: Introductionmentioning
confidence: 99%
“…Polyurethane replicas have been used previously for this purpose. Their anatomical characteristics, isotropic properties, modulus of elasticity, and density have been claimed to be similar to those of the human mandible . However, they were not available for this study.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, studies have been conducted on simulated bone models. Polyurethane was found to present elastic modulus similar to human bone (Miyashiro et al, 2011;Moretti-Neto et al, 2011) and was chosen to verify the tension levels that are developed around implants during function (Figure 8) When prosthetic restorations were connected to the abutments, the tension levels on the bone located at the cervical area of the implant were very low, around 58 με to 100 με for single crowns and reaching 350 με to 400 με for multiple element restorations. What can be regarded as relevant in these studies is that the tension levels fall within physiologic limits, as proposed by Frost's minimal effective strain theory, between 50-200 με to 1500-2500 με.…”
Section: Strain Gauge Analysismentioning
confidence: 99%